2020
DOI: 10.1093/pcmedi/pbaa010
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility-guided bismuth quadruple therapies for resistant Helicobacter pylori infections

Abstract: Increasing Helicobacter pylori resistance to antibiotics has led to adoption of seven different bismuth quadruple therapies (BQT) in China without differentiation of first-line or second-line regimens. The objective of this study was to evaluate the efficacy of susceptibility-guided BQT for patients who had experienced previous treatment failures. A total of 133 patients was included and H. pylori was successfully cultured from 101 patients (75.9%) for subsequent antimicrobial susceptibility testing (AST). Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…In view of the extremely high primary and secondary CLR resistance, the CLR-based regimens (even with the addition of bismuth) are no longer suitable as empiric treatment therapies for pediatric patients in Southwest China. However, of note is that if CLR is known to be susceptible by antimicrobial susceptibility testing, this antibiotic can be confidently prescribed to achieve successful H. pylori eradication ( Jones et al, 2017 ; Tang et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the extremely high primary and secondary CLR resistance, the CLR-based regimens (even with the addition of bismuth) are no longer suitable as empiric treatment therapies for pediatric patients in Southwest China. However, of note is that if CLR is known to be susceptible by antimicrobial susceptibility testing, this antibiotic can be confidently prescribed to achieve successful H. pylori eradication ( Jones et al, 2017 ; Tang et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the limited number of antibiotics that are appropriate for H. pylori eradication in children, and the worldwide increase of antibiotic resistance, the recent ESPGHAN/NASPGHAN guidelines have recommended antimicrobial susceptibility testing to guide the H. pylori eradication treatment in children ( Jones et al, 2017 ). However, due to the fastidious culture of H. pylori and the lack of an easy and cost-effective testing method, antimicrobial susceptibility testing for H. pylori is almost universally unavailable in medical centers ( Montes and Pérez-Trallero, 2017 ; Li et al, 2019 ; Tang et al, 2020a , b ). Under such circumstances, profiling regional or population-specific antibiotic resistance patterns is of great importance in guiding the development of effective empiric treatment regimens.…”
Section: Introductionmentioning
confidence: 99%
“…With whole‐genome sequencing and susceptibility testing of 59 H . pylori clinical isolates by E‐test, our group has recently shown that point mutations in 23S rRNA correlated 91.2% with the phenotypic clarithromycin resistance, while the gyrA point mutations correlated 82.3% with the phenotypic levofloxacin resistance 6 . In another recent study, the congruence between the phenotypic AST results by E‐test and the molecular susceptibility testing results by whole‐genome sequencing on 140 H .…”
Section: Prediction Of Antimicrobial Susceptibility Using Molecular M...mentioning
confidence: 98%
“…The standard methods that have been used for H. pylori AST include agar dilution test, [9][10][11][12] disk diffusion test, [13][14][15][16][17][18] gradient E-test, 6,13,16 and broth microdilution test. [19][20][21][22][23] All these methods require isolation of viable H. pylori relying on specific microbiology skills in the clinical laboratory to grow this fastidious microaerophilic bacterium over a period of 1-2 weeks.…”
Section: The S Tandard Antimicrob Ial Suscep Tib Ilit Y Te S Ting For...mentioning
confidence: 99%
See 1 more Smart Citation